Effect of plasma-activated water on the structure and in vitro digestibility of waxy and normal maize starches during heat-moisture treatment. (15th February 2020) - Yan, Yizhe; Feng, Linlin; Shi, Miaomiao; Cui, Chang; Liu, Yanqi
Highlights: Combined effect of plasma-activated water with heat-moisture treatment was studied. Structure and properties of waxy and normal maize starches were obviously modified. Resistant starch content of starches by combined modification was increased. Acidic species in plasma-activated water is an important factor for modification. Abstract: The combined effects of plasma-activated water (PAW) and heat-moisture treatments (HMT) on the structure, physicochemical properties and in vitro digestibility of waxy (WMS) and normal maize starches (NMS) were investigated. X-ray diffraction results revealed that the relative crystallinity of starches treated with PAW-HMT increased without crystalline type transition compared to DW-HMT. Through the Fourier transform infrared spectroscopy and Raman spectroscopy, the short-range order of starches treated with PAW-HMT was improved. Differential scanning calorimetry analysis shown that PAW-HMT increased gelatinization temperatures for NMS while decreasing gelatinization temperatures for WMS. The solubility of starches treated with PAW-HMT was higher than that of DW-HMT while the swelling power decreased. Importantly, the resistant starch (RS) content of starches treated by PAW-HMT increased compared to the starches treated by DW-HMT or native starch. This study provides a novel green method to modify the structure, lower starch digestibility and improve the RS content of starch.